Hubungan Simulasi Kesiapsiagaan Dengan Tanggap Darurat Gempa Bumi Pada Mahasiswa Stikes Tri Mandiri Sakti Bengkulu - trianopi herdiani (HEALTH CARE : JURNAL KESEHATAN, 2022)
Indonesia is one of the countries prone to disasters, this condition is because geographically Indonesia is an archipelagic country which is located at the confluence of four tectonic plates namely the Asian continental plate, the Australian continent, the Indian oceanic plate and the Pacific ocean. This study aims to study the relationship between preparedness simulation and earthquake emergency response in STIKES Tri Mandiri Sakti Bengkulu students. This type of research is an analytic survey with a cross-sectional design. The population in this study were 127 students of STIKES Tri Mandiri Sakti Bengkulu. Sampling in this study using accidental sampling technique. Statistical test using Chi-Square (X2). The research results show that from 127 respondents, there were 44 people who were less responsive to earthquake emergencies, and 83 people who were responsive to earthquake emergencies. Of the 127 respondents, 39 people had never participated in a simulation and 88 people had participated in a simulation. There is a significant relationship between preparedness simulation and earthquake emergency response for Tri Mandiri Sakti Bengkulu STIKES students. It is hoped that Tri Mandiri Sakti Bengkulu STIKES students can take part in earthquake preparedness simulation activities and educational institutions can collaborate with institutions, professional organizations and the government in improving disaster emergency response.